Analysis of Trass Stone Inventory Control With EOQ and JIT Methods - Saputra, Mochamad Ramadhan Indra; Widyaningrum, Dzakiyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
PT ABC is a company engaged in the cement manufacturing industry. In making cement at PT ABC, one of the raw materials used is Trass Stone. PT ABC in carrying out its production process from raw materials to finished goods experiences problems in the supply of raw materials which are sometimes excess or deficient. From these problems it is necessary to analyze the control of trass stone inventory using the Economic Order Quantity (EOQ) and Just In Time (JIT) approaches to control the optimal and efficient trass stone inventory, because it can calculate the amount of inventory, safety stock, and total inventory costs. The results showed that using the Economic Order Quantity (EOQ) and Just In Time (JIT) methods is more optimal and efficient than company policy. It can be seen from the total inventory cost of trass stone using company policy of Rp. 22,442,213, the total cost of trass stone inventory using the EOQ method is Rp. 10,269,996, while the total cost of trass stone inventory using the JIT method is Rp. 7 ,480,737.